KEEFEKTIFAN PEMBELAJARAN BERBASIS PENDIDIKAN KEWIRAUSAHAAN BERBANTUAN BUKU PANDUAN MOTIVATIF DALAM MENINGKATKAN KEMAMPUAN MENULIS CERITA PENDEK - Sudiyati Sudiyati (PBSI, FKIP UNISSULA, Semarang, 2017)
This research focused on entrepreneurship education-based learning within motivation guidebook. Purpose of the research was to determine the effectivity ofthe entrepreneurship education-based learning within motivation guidebook onstudents’ short story writing skill. This research was a quantitative type of research. It was conducted to students of grade XI in SMA Negeri 6 Semarang. Data collection method was a short story writing test. Data analysis was conducted by t-test formula to determine whether there was an improvement before and after the treatment. Result of the research indicated that value of tcount was 6.62 and on 5% significance, n = 30, ttable = 1.68. The tcount was higher than t-table, meaning that ha was acceptable. Thus, the learning of entrepreneurship education-based short story writing within motivation guidebook was effective to develop short story writing skill.